Governance paradigms of public universities: An international comparative study - Christopher, Joseph (Kluwer Academic Publishers, 2012)
This study aims to develop a conceptual model of the wider influencing forces impacting the governance paradigms of public universities. It draws on the multi-theoretical governance concept and seeks to identify these forces through the lens of chief audit executives using a qualitative research approach. The interview data supported by published literature reveal universities are affected differently by a number of common influencing forces, resulting in different governance paradigms. These findings provide insights as to the causal factors that shape a public university’s governance paradigm. The practical implications of the findings are that these forces need to be taken into account in future governance studies of universities as it provides the basis to determine their stakeholder base; consequent contractual obligations with them; and the governance control mechanisms and processes to be developed and implemented at the board, operational and assurance levels of governance.